A Homossexualidade e a AIDS no Imaginário de Revistas Semanais (1985-1990) - Soares, Alexandre Sebastião Ferrari (2006)
This work is a result of research into the function of jornalistic discourse regarding homessexuality and its relationship to AIDS (Acquired Immune Deficiency Syndrome) in the second half of the 1980s according to French Discourse Analysis. The analysis of language material is what allows the comprehesion of meanings which derive from the impression made by language in history. This discursive process becomes what is called naturalization of meanings produced by ideology, which puts humanity in an imaginary relationship with the material conditions of its existence. Thus the discourse not only affects the subject but creates him. The clippings on which this research is based from the magazines Veja, Istoé and Superinteressante focus on the realms of meaning in journalistic discourse on homosexuality: medical, religious and legal discourses, which came together so in such a way that homosexuals themselves followed this paradigm. Homosexual came to mean sin and illness and to approximate to AIDS. In this new set of circumstances (the AIDS epidemic) the homosexual was allowed a space to talk about himself, but this space was restricted to discursive official areas concerning AIDS: sexuality, contamination, promiscuity and lifestyle. The discursive sequences, including letters from readers and analysed photographs, in this research contribute to the permanency of historical legitimated meanings for homosexuals. Journalistic discourse has a fundamental role in this construction of meanings which, under cover of an illusory pretence of neutrality and veracity, etc., created discourses which while they passed themselves off as being the homosexual and his lifestyle, assigned to him responsibility for the illness and for its propagation.